2019
DOI: 10.1038/s41598-019-44398-7
|View full text |Cite
|
Sign up to set email alerts
|

Time-restricted feeding improves adaptation to chronically alternating light-dark cycles

Abstract: Disturbance of the circadian clock has been associated with increased risk of cardio-metabolic disorders. Previous studies showed that optimal timing of food intake can improve metabolic health. We hypothesized that time-restricted feeding could be a strategy to minimize long term adverse metabolic health effects of shift work and jetlag. In this study, we exposed female FVB mice to weekly alternating light-dark cycles ( i . e . 12 h shifts) combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Furthermore, dark-phase TRF normalized clock gene expression in diabetic mice of which the daily rhythm in locomotor was dampened and clock gene rhythms were shifted (84). TRF can help adapt to a changing light-dark schedule, hence providing a promising strategy to expedite adaptation of the circadian system (85) or to prevent shifting during shift-work.…”
Section: Time-restricted Feeding (Trf)mentioning
confidence: 99%
“…Furthermore, dark-phase TRF normalized clock gene expression in diabetic mice of which the daily rhythm in locomotor was dampened and clock gene rhythms were shifted (84). TRF can help adapt to a changing light-dark schedule, hence providing a promising strategy to expedite adaptation of the circadian system (85) or to prevent shifting during shift-work.…”
Section: Time-restricted Feeding (Trf)mentioning
confidence: 99%
“…The beneficial effects of TRF on mood regulation may be related to the entraining properties of food in phase with activity which prevents circadian disruption and enforces circadian function (Salgado-Delgado et al, 2010Schilperoort et al, 2019). Previous Other studies have suggested that the beneficial effects of TRF may not only be related to the reestablishment of the molecular circadian clock function on metabolic related organs, since TRF drive the rhythmic expression certain genes even in mutant mice (Atger et al, 2015;Vollmers et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of TRF on mood regulation may be related to the entraining properties of food in phase with activity which prevents circadian disruption and enforces circadian function (Salgado‐Delgado et al., 2010, 2013; Schilperoort et al., 2019). Previous studies demonstrated that food elicited signals entrain brain areas involved in metabolic function (Ramirez‐Plascencia et al., 2017) as well as areas related with mood regulation (Angeles‐Castellanos et al., 2008; Verwey & Amir, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning with preclinical research, studies of mice have shown that restricting food access to the dark period (the active phase for these nocturnal animals) may protect against the obesogenic effects of repeated 6-h advances in the LD cycle (48). In addition, restricting food access to the active phase may also accelerate adaptation of circadian rhythms in core body temperature and locomotor activity to repeated 12-h changes in LD cycles (49). These findings imply that people would better cope with rotating shift work if they fixed their eating to the daytime, which is somewhat counterintuitive given that fixing eating time during shifting LD cycles might be expected to uncouple circadian rhythms between the suprachiasmatic nucleus and peripheral clocks.…”
Section: Diet Timing In Shift Workersmentioning
confidence: 99%